Analysis of Diversion Capacity of Yellow River Diversion Sluices in Irrigation Areas of Lower Yellow River - Li Ziming; Zheng Yanting; Bai Yunsheng (E3S Web of Conferences, 2023)
This paper analyzes the influence on the diversion capacity of the Yellow River diversion sluices of factors such as the diversion water level change of the Yellow River diversion sluices in the irrigation areas of the lower Yellow River, the scouring of river channels and the siltation change in the diversion channels. It is suggested that the main reason for the decrease in diversion capacity of the Yellow River diversion sluices in different inflow levels is the obvious decrease in the water level of the same discharge due to the continuous scouring of river channels. At the end of this paper, targeted countermeasures and suggestions are put forward to solve the problem of the water diversion capacity decline of Yellow River diversion sluices.